ANALISIS PENERAPAN QRIS PADA UMKM KONTER BRIJO CELL DAN SEBLAK LUSEYKA HOUSE - Asya Adinda Prianitha; Martinus Budiantara (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The study aims to identify the implementation of the Quick Response Code Indonesian Standard (QRIS) in supporting transaction activities and financial record-keeping at Konter Brijo Cell and Seblak Luseyka House MSMEs. The study applied a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings indicate that the use of QRIS provides convenience and improves transaction efficiency because payment can be carried out more quickly and practically through cashless methods. Furthermore, QRIS assist business owners in monitoring transactions through automatically stored digital transaction data. However, the implementation of QRIS has not been fully optimized since financial records are still managed manually and have not yet been integrated into digital systems. Several obstacles were also identified, including limited technological understanding and unstable internet connectivity that affects transaction processes.